MAKNA SEJAHTERA PADA KELUARGA YANG MENERAPKAN SALAT BERJAMAAH DI MASJID DESA AENG PANAS PRAGAAN SUMENEP - Fitria Amarina (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
Building a prosperous home life is every human's dream, but of course achieving it is not an easy matter. Because this requires readiness in many things, especially in terms of religious knowledge, something that a wife must have, especially the husband as head of the family. Prosperity in the family is something that many people hope for, so to achieve this it requires a long effort and struggle, of course each family has a different way to achieve it, this can be done by offering congregational prayers at the mosque for the family even though they cannot do it five times a day only. certain obligatory prayers such as Asr or Maghrib and Isha' prayers. implementation of congregational prayers among families who practice congregational prayers at the mosque in Aeng Panas village? And what is the meaning of congregational prayer for families who pray together at the mosque in Aeng Panas village? This research uses qualitative research with a phenomenological design, as well as data collection methods using observation and interviews. The data analysis method used is by presenting the data, conducting epoche, presenting the data, verifying and concluding. Using Ellison's theory of Spiritual Well- being, this theory is used because it can provide a clear conceptual understanding of the various views expressed in spirituality in society. This research resulted in the following findings: 1. Implementation of congregational prayers in families who implement 3 congregational prayers, namely: 1. Istiqamah for Asr, Maghrib and Isha'ah prayers in congregation at the mosque. 2. Istiqamah perform the morning, Maghrib and Isha' prayers in congregation at the mosque. 3. Istiqamah: Subuh, Midday, Asr, Maghrib and Isha' prayers in congregation at the mosque. 2. There are also 3 meanings of prosperity for families who practice congregational prayers at the mosque, namely: 1. Feeling that they are sufficient with everything that is given to them, including the necessities of life as a family. 2. Peace with the family, even if there is a disagreement, it can be resolved well without having to argue with each other. 3. Godly children who are obedient in religious matters and obey their parents.